ANALISIS HASIL TANGKAPAN SET NET JENIS OTHOSIAMI DI TELUK MALASSORO, SULAWESI SELATAN - Olii, M Yasin U.P; Baskoro, Mulyono S; Martasuganda, Sulaeman; Mawardi, Wazir (Jurnal Teknologi Perikanan dan Kelautan, 2015)
Set net is a fishing gear to set permanently in the fishing ground. Set net othosiami was developed by Center for Fisheries Development Department of Marine and Fisheries (BPPI) Semarang; it had been operated in 2010 at the Gulf Mallasoro, Jeneponto. The data information was collected regarding productivity, compositioning and catching diversity was taken from the catching data in 2011-2013. The study aims were to analyze catching trend, catching composition types and catching diversity. This study was conducted on January and February 2014 at the Gulf Mallasoro, Jeneponto. The method was used descriptive method. Based on the data from 2011-2013 on September-October showed a decline catching trend while the amount of cacthing trend consisted to 91 species. The pelagic fish has been identified for 31 species and 26 species belongs to demersal fish out of 57 species were found. The most dominant fish was Peperek (Leiognathus splendens) with 27% of catched fishes. The diversity index (H’) catching fish period 2011-2013 ranged from 2.61 – 2.74 which regard to moderate category diversity. Furthermore, the value of evenness index (E) was more evenly 0.63 - 0.70 categorical. The dominance index value (D) showed within 0.12 to 0.15 there was no dominant species.